Serum protein concentrations in calves with experimentally induced pneumonic pasteurellosis - Fagliari,J.J. (2003)
Ten healthy 2 to 4-week-old Holstein calves were randomly allotted into control and infected groups. Control calves (n=5) were inoculated intrabronchially with 5ml of Dulbecco's phosphate-buffered saline solution (DPBSS). Infected calves (n=5) were inoculated intrabronchially with 5x10(9) log-phase Mannheimia haemolytica organisms suspended in 5ml of DPBSS. Blood samples were obtained 15 minutes before and one, two, four and six hours after inoculation. Serum protein concentrations were determined by means of sodium dodecyl sulphate-polyacrylamide gel electrophoresis. Serum concentrations of proteins with molecular weights of 125,000 D (ceruloplasmin), 60,000 D (a 1-antitrypsin), 45,000 D (haptoglobin), and 40,000 D (acid glycoprotein) were significantly increased in calves with pneumonic pasteurellosis, compared with concentrations in control calves. Results indicate that acute phase proteins increase more rapidly after the onset of inflammation than previously thought. Measurement of serum protein concentrations may be useful in monitoring the progression of the induced pneumonic pasteurellosis in calves.